POPULATION OF THE REPUBLIC OF KARAKALPAKSTAN AND ITS DEMOGRAPHIC INDICATORS - Egamkulov Khusniddin Erkaboevich; Pulatova Sokhiba Ergash kizi (Western European Studies, 2025)
The population and its dynamics in the Republic of Karakalpakstan have been analyzed, and the demographic changes observed over the years have been thoroughly studied. Population growth trends, birth and death rates, as well as the differences between them, have been statistically analyzed. Additionally, the ratios of fathers and mothers in relation to birth rates were determined, and their impact on demographic processes was evaluated
Keywords: population; demographic indicators; birth rate; mortality